Analysis of shear characteristics of woven fabrics and their interaction with fabric integrated structural factors. (August 2019) - Shanbeh, Mohsen; Safar Johari, Majid; Zarrebini, Mohammad; Barburski, Marcin; Komisarczyk, Agnieszka
Behavior of woven fabrics during complex deformations is most influentially affected by their shear behavior. Shear characteristics of woven fabrics can be explained by fabric shear rigidity and shear hysteresis. In this study, the effects of weft density, weft count, and fiber type on shear behavior of woven fabrics in the principal directions of fabric were statistically evaluated. Statistical methods such as multiple linear regression analysis, univariate test, and correlation analysis were also applied. The univariate test results confirmed that the weft density is the most dominant parameter that affects fabric shear properties. Multiple linear regression results point to poor shear behavior in woven fabrics with cotton weft yarns. In addition, correlation between the shear rigidity of the fabrics along principal directions with the Milasius fabric firmness factor and the fabric cover factor as integrated structural parameters was established. High correlation was found to exist among Milasius fabric firmness factor, fabric cover factor, and shear rigidity of fabrics along principal directions.